Academic Leaders’ Perspectives on Entrepreneurship at Finnish Universities : A Comparative Case Study - Hytti, Ulla; Montonen, Tero; Eriksson, Päivi; Peura, Kirsi (Sage, 2025)
This case study focuses on academic leaders’ perspectives regarding entrepreneurship at two Finnish universities. It illustrates how university rectors and deans representing a multiplicity of academic traditions make sense of divergent ideas and expectations about what kind of entrepreneurship is sought and implemented in their university. Academic leaders’ understandings are important because they influence how entrepreneurial activities are approached and adopted as part of university strategies and policies. The entrepreneurial university concept undergirds the theoretical frame of the study. Through 15 interviews with academic leaders (rectors and deans) at two multi-faculty universities in Finland, we conduct a narrative analysis of meanings attached to entrepreneurship in the context of universities’ societal impact. The findings highlight how entrepreneurship is presented simultaneously as necessary for all but limited to some disciplines and individuals. Furthermore, adopting a future-oriented perspective allows entrepreneurship to be depicted as important for the younger generations, though not requiring actions by decision-makers presently.